2021
DOI: 10.1259/bjr.20201415
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow quantification estimated by dynamic 320-detector CT angiography: validation by 13N ammonia PET myocardial flow reserve

Abstract: Objectives: Resting coronary flow index (rCFI) estimated by 320-detector low-dose dynamic coronary CT angiography (CCTA) is a direct flow quantification using intracoronary attenuation. We propose modified-rCFI from new protocol combining dynamic scan and standard CCTA using dose-modulation, and validate its consistency with quantitative values and ischemia depicted by 13N-ammonia PET (NH3-PET). Methods: 46 patients who underwent dynamic CCTA and NH3-PET for coronary artery disease were evaluated using origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Using the previously reported maximum slope method [1] , [24] , we analyzed the time-attenuation curve of the evaluated coronary arteries based on the same dynamic CCTA data and presented the results of the coronary flow index calculation. The coronary flow indices for RCA#3, LAD#8, and LCX#13 were 0.90 ± 0.26, 0.82 ± 0.22, and 0.82 ± 0.20, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using the previously reported maximum slope method [1] , [24] , we analyzed the time-attenuation curve of the evaluated coronary arteries based on the same dynamic CCTA data and presented the results of the coronary flow index calculation. The coronary flow indices for RCA#3, LAD#8, and LCX#13 were 0.90 ± 0.26, 0.82 ± 0.22, and 0.82 ± 0.20, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been reported that dynamic CCTA scanning can estimate functional myocardial ischemia [35] and can also estimate myocardial blood flow via ammonia PET [1] . The scan protocol used in this study, which combines standard CCTA with low-dose dynamic imaging using a 320-row scanner, does not increase radiation exposure as compared to conventional CCTA [23] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations